Structural processes in Gabriel Fauré's nocturnes for piano - Rooi, Pieter (College of Music, 2021)
This study constitutes an investigation of Gabriel Fauré's achievements in the genre of the piano nocturne through detailed analysis of each of his thirteen nocturnes. Fauré's nocturnes are widely considered to be representative of his pianistic style and musical language, showing a great spectrum of compositional procedures and covering the different stages of his life. The investigation is contextualised through a history of nocturne form, a biographical background of the composer, an overview of the three compositional stages in his life and of various aspects of his musical style, comparisons with the music of Fauré's predecessors and contemporaries and with the rest of his oeuvre, and a general appraisal of the contributions of other authors and scholars in the field. As a corpus, the nocturnes form a unique contribution to the genre, and, especially in the larger-scale examples, a more complex structure than one encounters in the examples by other exponents of the nocturne such as Field, Chopin, Liszt, Balakirev, Scriabin, Satie, Debussy and Poulenc. The investigation focuses on a close reading of the nocturnes, and especially on thematic, motivic and harmonic usage, and on Fauré's most original contribution, his complex integration of advanced chromaticism and extended modal procedures. The latter, which include the use of modes of non-diatonic scales and modes on altered degrees, have received hardly any scholarly attention, despite constituting a highly significant contribution to musical thought. By treating harmonic features as referential elements, Fauré creates a complex interaction between harmonic and structural procedures which greatly advances the scope and structural integration of the nocturne